Family scenarios and violence: a clinical case story - Ferrari Bravo, Gabriella; Arcidiacono, Caterina (La camera blu. Rivista di studi di genere, 2014)
This article describes the acceptance and taking-charge process of a history of incest involving a father and his daughter. This case arrived through an ad hoc telephone line set up by a territorial service aimed at listening, counselling, and treating problems and conflicts inherent in family life. The mother made the first contact with this service, ten years after the event. The case story is geared to outlining the development of the relational events within the parents‟ relationship and in relation to their daughter as well as the interactions with the family service (CPF). The purpose is also to show the procedure of the intervention and taking-charge process carried out by the psychologists of the service as well as the counter-transference feelings that have accompanied the clinical intervention and the effects they have had on the relationships between the individual members of the whole family.